Assessing the Effect of Hyperbaric Oxygen Therapy on Heart Rate and Blood Pressure - Patmah Fatoni; Ainun Ni’mah Milenia Gusti; Lucia Kusumawati; Evelyn Djiuardi; Roderick Osman Chandra (Interdisciplinary Journal of Advanced Research and Innovation, 2025)
Cardiovascular diseases (CVDs) are the leading cause of global mortality, encompassing heart disease, strokes, and related conditions. To combat this public health concern, monitoring vital indicators like heart rate and blood pressure plays a pivotal role in early detection, preventive care, treatment assessment, fitness tracking, and post-surgery care. This study aims to assess the effect of Hyperbaric Oxygen Therapy on heart rate and blood pressure, exploring its potential role as a therapeutic intervention to optimize cardiovascular system health. This study examines the effects of hyperbaric oxygen therapy (HBOT) on heart rate and blood pressure in patients who receive multiple treatments. The research includes 113 participants undergoing HBOT at different frequencies over 2 weeks. This study used specific statistical tests to analyze the effects of Hyperbaric Oxygen Therapy (HBOT) on heart rate and blood pressure. For nonparametric data, the Wilcoxon test will be employed, and for normally distributed data, the Paired T-test will be used. To determine the most influential HBOT frequencies group, the Kruskal- Wallis test will be applied due to the delta heart rate categorized as ordinal. The statistical analysis revealed a significant difference in heart rate before and after HBOT treatment with frequencies of two, three, and five times a week with the details p = 0.008, p < 0.001, and p < 0.001, respectively. As for heart rate alterations, HBOT should be administered at least three or five times a week, which led to notable reductions in heart rate. The correlation values on systole and diastole before and after treatments are 951 and 916 respectively. This data shows that hyperbaric oxygen therapy does improve the blood pressure quality of hypertensive patients. By examining the effect of HBOT on heart rate and blood pressure, this study seeks to contribute valuable insights to the field of cardiovascular system health and provide evidence for the use of HBOT in promoting healing and well-being.